Exchange-rate exposures of Singapore listed companies - Lee, Kee Hwa (2009)
This study examines the long-term economic exposures of Singapore listed companies using the "flow" approach and the "stock" approach. On average, economic exposures were found to be significant in a small number of companies. However, the companies that had statistically significant exchange-rate exposures had considerable degrees of exposures. Among the sample companies, more companies were found to have positive exposures. In both measures of economic exposures, neither industry nor firm size was identified as a variable that could explain the differences in economic exposures. Furthermore, both measures of economic exposures were found to be independent of each other, hinting that market-formed judgment about the impact of changes in exchange rates on the profitability of companies plays a key role in determining the share prices of individual companies.